Pengaruh Kompensasi, Gaya Kepemimpinan, Dan Disiplin Kerja Terhadap Kinerja Pegawai (Studi Kasus Pt. Zarnita Abadi) - Ardiansyah; Maulidar (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
This study aims to analyze the effect of compensation (X1), leadership style (X2) and work discipline (X3) on employees performance (Y) in PT. Tirta Investama, Pondok Pinang. The samples were obtained by purposive sampling method, and selected 49 respondents as a sample. While the analysis of the data used in his research include: quality test, classic assumption test, multiple liner regression analysis and hypotheses test. Results partial significance test (t statistic test) of the analysis and discussion research shows that: 1) compensation, with tvalue 0,536 <ttabel 1,677 and significant value of 0,595. By using the limit of significance of 0,05, then 0,595 > 0,05. This means that compensation (X1) had no a significant influence on performance employees partially. 2) leadership style, with tvalue 3,718 >ttabel 1,677 and significant value of 0,001. By using the limit of significance of 0,05, then 0,001 < 0,05. This means that leadership style (X2) had a significant influence on performance employees partially. 3) work dicipline, with tvalue 3,949 > ttabel 1,677 and significant value of 0,000. By using the limit of significance of 0,05, then 0,000 < 0,05. This means that work discipline (X3) had a significant influence on performance employees partially. While results simultaneous significance test (F statistic test) shows that Fvalue 10,632 > Ftabel 2,79. This means that the variables of compensation (X1), leadership style (X2) and work discipline (X3) simultaneously had significant influence on employees performance (Y).